Developing Indonesian Instructional Materials for Lower-Grade Students of Elementary Schools Throughout Bali: An Ethnopedagogic Study - Rasna, I W (KnE Social Sciences, 2018)
This research was designed using research and development (RD) following the procedure of Borg and Gall. The procedure consisted of a preliminary study, planning, learning materials development, expert judgment, and a small-scale trial. Data were gathered through a document study, a questionnaire, and observation. The data were analyzed using both quantitative and qualitative descriptions. The results of data analysis show the development of an integrated theme-based course book. The children’s responses indicated that they understood well the learning materials contained in the book. The children were also able to show good social competence. Keywords: learning material, local wisdom, social reconstruction